1994
DOI: 10.1109/12.338107
|View full text |Cite
|
Sign up to set email alerts
|

Bit-serial multipliers and squarers

Abstract: Traditional bit-serial multipliers present one or more clock cycles of data-latency. In some situations, it is desirable to obtain the output after only a combinational delay, as in serial adders and subtracters. A serial multiplier and a squarer with no latency cycles are presented here. Both accept unsigned or sign-extended two's complement numbers and produce an arbitrarily long output. They are fully modular and thus good candidates for introduction in VLSI libraries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…This would again lead to additional delay cycles in the mprod and euclidean operations, where the accumulation is performed on the longest data word of the system. An improved multiplication scheme was therefore developed for two's complement numbers [9]. The corresponding circuit is presented in Fig.…”
Section: Arithmetic Unitmentioning
confidence: 99%
“…This would again lead to additional delay cycles in the mprod and euclidean operations, where the accumulation is performed on the longest data word of the system. An improved multiplication scheme was therefore developed for two's complement numbers [9]. The corresponding circuit is presented in Fig.…”
Section: Arithmetic Unitmentioning
confidence: 99%
“…When analyzing the squarer in Fig. 2, it was found that the resemblance to a bit-serial squarer [6] [7] is large. By introducing registers in the design of the bit-serial squarer the partial results of x n 2 is easily extracted.…”
Section: B Processingmentioning
confidence: 99%
“…This method needs only cells for an n-bit multiplication but it introduces an XOR gate in the critical path, which ends up with a more complicated overall design. Lenne et al [3] designed a bit-serial-serial multiplier that is modular in structure and can operate on both signed and unsigned numbers.…”
Section: Review Of Serial Multipliersmentioning
confidence: 99%